Bifunctional Pancharatnam‐Berry Metasurface with High‐Efficiency Helicity‐Dependent Transmissions and Reflections. Issue 1 (2nd November 2017) - Cai, Tong; Wang, Guang‐Ming; Xu, He‐Xiu; Tang, Shi‐Wei; Li, Haipeng; Liang, Jian‐Gang; Zhuang, Ya‐Qiang
Abstract: Manipulating circularly‐polarized (CP) waves in desired multi‐prescribed manners, especially in both transmission and reflection schemes, in a single flat device is of particular importance in photonic integration, imaging processing and communication systems. However, available approaches suffer from large thickness, low efficiencies as well as limited wavefront control spaces. Here, we propose a general strategy by using specially tailored Pancharatnam‐Berry (PB) meta‐atoms with helicity‐dependent transmissions and reflections to design high‐efficiency CP bifunctional metasurfaces. As a proof of the strategy, two metadevices are designed and characterized at microwave frequencies: the former one achieving focusing/diverging lenses at transmission/reflection side of the metasurface; the latter one realizing CP beam separation under illuminations of CP waves with different chirality, respectively. Both numerical and experimental results demonstrate the predicted EM functionalities, and all these functionalities exhibit very high efficiencies (88%∼94%). Our findings afford a new route to design high‐performance CP bi‐functional metasurfaces operating in other frequency domains or with other functionalities. Abstract : Manipulating circularly‐polarized (CP) waves in desired multi‐prescribed manners, especially in both transmission and reflection schemes, is of particular importance. Here, we propose a general strategy by using specially tailored Pancharatnam‐Berry meta‐atoms with helicity‐dependent transmissions and reflections to design high‐efficiency CP bifunctional metasurfaces. As a proof of the strategy, two bifunctional metadevices are designed and characterized at microwave frequencies, and both of them exhibit very high efficiencies (88%∼94%).